Axiological dimensions of family discourse: A qualitative analysis of women’s blogs in Russian and Serbian digital spaces - V. Leontyeva, Tatyana; Shchetinina, Anna; Jevtović, Zoran (Sociološki pregled, 2026)
This study examines the representation of family values within the context of women’s blogging in Russia and Serbia. Methodologically, the study employs content analysis, a phenomenological approach, and an axiological framework for interpreting blogging narratives. It is posited that the frequency of a blogger’s engagement with specific thematic domains in text posts, videos can be conceptualized as an empirical indicator of their dominant value orientations. Key values identified in the women’s blogs include: Children, Joint family travel, Joint family celebrations, Household management, etc. It is noted that these values are typically not explicitly labelled within the narrative but are present implicitly. Significant similarities were found in the coverage of family themes across the Russian and Serbian blogospheres.